2006
DOI: 10.1186/1471-2105-7-s5-s10
|View full text |Cite
|
Sign up to set email alerts
|

Trends in life science grid: from computing grid to knowledge grid

Abstract: Background: Grid computing has great potential to become a standard cyberinfrastructure for life sciences which often require high-performance computing and large data handling which exceeds the computing capacity of a single institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…Not every programmer codes in the same way, and it may be that they have a tacit, rather than codified, understanding of how the system is structured and how it is to be maintained. While Konagaya (2006) has argued that knowledge grids could be designed 'for sharing tacit knowledge among a community', the individual stylization of programming can nevertheless cause problems for long-term maintenance of biological databases.…”
Section: Maintenancementioning
confidence: 99%
“…Not every programmer codes in the same way, and it may be that they have a tacit, rather than codified, understanding of how the system is structured and how it is to be maintained. While Konagaya (2006) has argued that knowledge grids could be designed 'for sharing tacit knowledge among a community', the individual stylization of programming can nevertheless cause problems for long-term maintenance of biological databases.…”
Section: Maintenancementioning
confidence: 99%
“…Grid technology allows users to have access to services without knowledge of, or expertise with, or control of the infrastructure which supports them. Recently, grid technology has been embraced by the field of biomedicai informatics [20] for research purposes particularly in imaging informatics and translational clinical research [21]. Grid computing applied to the public health domain has currently been on the rise and each of these study has demonstrated the potential benefits of leveraging grid technology in the public health domain [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…A virtual grid resource specification captures the desired resources for an application, and its explicit resource structure can be used by the application designer to express parallelism, communication, and other forms of optimization. The primary goal of grid computing platforms is to seamlessly multiplex distributed computational resources with its associated providers and end users across wide area networks [12]. In traditional computing environments, resources are multiplexed based on typical operating systems confined to limited resources.…”
Section: Introductionmentioning
confidence: 99%